Efficacy and Safety of Moxibustion for Postherpetic Neuralgia: A Systematic Review and Meta-Analysis - Wu, Qiqi; Hu, Hantong; Han, Dexiong; Gao, Hong (Frontiers in Neurology, 2021)
Background: Postherpetic neuralgia (PHN) is one of the most common complications of herpes zoster (HZ), and there is still a lack of effective therapies. An increasing number of studies have found that compared to traditional therapy, moxibustion treatment is beneficial for the treatment of PHN, although current evidence remains inconclusive. This systematic review and meta-analysis of randomized controlled trials (RCTs) aimed to evaluate the efficacy and safety of moxibustion for PHN. Methods: We conducted a broad literature review in a range of databases from inception to December 2020, including the Cochrane Library, PubMed, EMBASE, Web of Science, Clinical Trails, China National Knowledge Infrastructure (CNKI), VIP Database for Chinese Technical Periodicals (VIP), China Biomedical Network Information, and Wanfang databases. We included RCTs that compared moxibustion with pharmacological therapies, herbal medicine, or no treatment, for treating PHN. The main outcome measure was efficacy rate and Visual Analogue Scale (VAS); the secondary outcome measure was adverse events. Data accumulation and synthesis included meta-analysis, publication bias, sensitivity analysis, risk-of-bias assessment, and adverse events. Results: We included 13 RCTs involving 798 patients. Compared with the controls (pharmacological therapies, herbal medicine, or no treatment), moxibustion achieved a significantly higher efficacy rate (odds ratio [OR]: 3.65; 95% [confidence interval]: [2.32, 5.72]; P < 0.00001). Subgroup analysis of the distinct moxibustion modalities showed that both Zhuang medicine medicated thread and thunder-fire moxibustions obtained higher clinical efficacy than the control group. Compared with the controls, moxibustion resulted in significantly lower scores on the VAS (Weighted Mean Difference (MD)  = −1.79; 95% CI: [−2.26, −1.33]; P < 0.00001). However, there was no significant difference in terms of safety between moxibustion and the controls (OR = 0.33; 95% CI [0.06, 1.77]; P=0.19). Conclusion: Due to the lack of methodological quality as well as the significant heterogeneity of the included studies, it remains difficult to draw a firm conclusion on the efficacy and safety of moxibustion for the treatment of PHN. Future high-quality studies are urgently needed.